A evolução biológica na formação inicial de professores de ciências e biologia: visões dos licenciandos e dos professores formadores - Lunardi, Larissa (2024)
Biological evolution is the integrative axis of biology, unifying and allowing a historical dimension for the science of life. However, studies show that, when approached, is worked in isolation in basic education, and in higher education the specific components of biology are not always presented in an evolutionary perspective. Thus, the objective of the study is to understand how the biological evolution is addressed in the initial formation of science and biology teachers, based on the visions of the undergraduates and formation teachers in a campus of a higher education institution in Rio Grande do Sul. Research was organized in four writings. A review was held in the annals of the National Meeting of Research in Science Education (ENPEC) and the National Meeting of Biology Teaching (Enebio) of the last 10 years (from 2012 to 2022) seeking works related to the research theme. It was also analyzed as the Common Curriculum National Base (BNCC), an current document that guides Brazilian curricula, treats biological evolution. Then, questionnaires were held with the Biological Sciences graduates of the investigated institution, to identify whether there are wrong conceptions about evolution and compare such conceptions with the semesters attended by the undergraduates. Finally, teachers forming the same course and institution were asked to understand whether biological evolution is characterized as a central axis in teaching the specific curriculum components of biology, as well as identifying how this theme is addressed by these teachers. This research has a qualitative approach and the analysis of the results was performed using the analysis of contents in the first three written and an essentially descriptive analysis in the latter. 1) From the investigation of the works at events, 21 research has been identified, and it is clear that difficulties and misconceptions related to evolutionary concepts are frequent, and formation is directly related to these challenges, the fragmentation of content and scarcity in discussions about nature of science and religious beliefs. 2) According to BNCC analyzes, eleven themes related to biological evolution were identified, six were present in the writings of the elementary school and ten in the high school, and it is found that the third and current version is The shallowest, with less mentions and diversity of themes related to the teaching of evolution. 3) In the responses of the undergraduates were identified mistaken conceptions, regardless of the semester attended, including those who were at the end of the course, both related to the concept of biological evolution and human evolution. 4) Finally, teachers claim to address evolutionary aspects during the classes of the different specific curriculum components. Some teachers also commented on having difficulty in planning classes due to their fragmented initial formation. Thus, it is believed that continuing education with all teachers of the course is required for the scope of new research and understanding of the latest concepts in the area of biological evolution.